Sharia Financial Literacy and Digital Literacy on Students’ Decisions to Use BSI Mobile - Citra, Mitra Julia; Fitriah, Rinna Ramadhan Ain (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This research is motivated by the fact that the level of sharia financial literacy among students is uneven, while digital literacy also determines their ability to access BSI Mobile. The purpose of this study is to examine how sharia financial literacy and digital literacy influence students’ decisions to conduct sharia transactions using BSI Mobile. The study employs a quantitative associative approach with survey data collected from 75 students of the Faculty of Economics and Business, Mulawarman University, using an online questionnaire. Data were analyzed using ordinal logistic regression to measure the significance of the independent variables. The results show that sharia financial literacy and digital literacy each have a significant positive effect on the decision to engage in sharia transactions. Simultaneously, the two literacies complement each other and become key determinants of sustainable adoption of Islamic financial technology among students. The originality of this study lies in integrating financial and digital literacy into one explanatory framework, while its implications provide practical insights for universities and Islamic banks to design integrated literacy programs.